Age heaping and numeracy: Looking behind the curtain - Matthias Blum; Karl-Peter Krauss (Queen's University Centre for Economic History (QUCEH), 2017)
Age heaping-based numeracy indicators have served as valuable tools to derive basic human capital estimates, especially for periods where other indicators are unavailable. However, the accuracy of individual age statements usually remains unknown, and due to the lack of precise information it can only assumed that excessive occurrence of multiples of five in age distributions reflects inferior numerical skills. We address this lacuna by identifying 162 individuals in two independent data sources, self-reported age statements and independently kept records which are based on family heritage books and church registers. This method allows us to identify individual misreporting and the degree of accuracy of each individual. We find that not everyone who reports a multiple of five reports an incorrect age, nor everyone who reports an age that is not a multiple of five reports an accurate age. In an empirical analysis we show that the commonly used binary numeracy indicator is correlated with the observed degree of accuracy in age statements, and that a more sophisticated occupational background reduces this inaccuracy. Our tentative results suggest that the commonly used binary indicator measuring age heaping is a valuable proxy of the numerical skills and occupational background in a population.
Keywords: N01; N33; C43; O15; 330; numeracy; ABCC; age heaping; human capital; inequality; economic history; skills; methodology; migration